THE IMPACTS OF GOVERNMENT AND MANAGEMENT CONFLICTING OBJECTIVES ON THE STATE-OWNED ENTERPRISES (SOEs) PERFORMANCES: THE CASE OF INDONESIA PUBLICLY LISTED SOEs - Fitriningrum, Andriati (Universitas Brawijaya, Indonesia, 2020)
Paper is aimed to examine the impacts of conflicting objectives on the StateOwned Enterprises (SOEs) performance. The study motivated by the potential differences between government as the shareholders and management as the operator of SOEs. Government as shareholders may include politician, bureaucrats, and other government's agents or ministry who have different interests and objectives toward SOEs. The government objectives are mainly dominated by socio-economic expectations. Meanwhile, management may bring his/her own interest and objectives which dominated by market and economic expectation. The conflict may appear and affect the performance. Using the case of the Indonesia public listed SOEs, this study examines in the extent to which the conflicting objectives between government and management stated objectives affect the performance; and which objectives dominate the business. The Statistic tools are used to examine the impacts of government and management conflicting objectives on SOEs performance during the period 0f 2004 to 2018. The period is selected particularly to see whether the changes of political regime contribute to the conflicting objectives. The study indicates that government objectives dominate the business activities which significantly affect the performance of SOEs.